HAK WARIS ISTRI DARI HARTA BAWAAN SUAMI PERSPEKTIF HUKUM ISLAM DI INDONESIA : STUDI KASUS PADA MASYARAKAT KAMPA - Ridha, Muhammad (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2025)
This research is motivated by the absence of clear discussion in the Al-Qur'an or hadith regarding the provisions on the wife's inheritance rights from inherited property that are implemented in Kampa District, Kampar Regency, meanwhile this tradition has become a problem in society, such as the birth of conflict, damage to social relations and so on. Therefore, it is necessary to review in depth the provisions on the wife's inheritance rights from inherited assets in Kampa District so that we can find out scientifically about how to implement the wife's inheritance rights from inherited assets, the reasons for how to distribute inherited assets and the view of Islamic law regarding how to distribute The wife's inheritance rights from inherited assets in Kampa District, Kampar Regency. This research is field research using qualitative descriptive research methods. The sample used in this research was 15 people, consisting of traditional leaders, community leaders, religious leaders and ordinary people, using the Purposive Sampling Method. From the research results, it can be understood that the wife's inheritance rights from inherited assets in the traditional provisions of Kampa District, Kampar Regency stipulate that the wife's inheritance rights from inherited assets are obtained by the family of the husband who dies, while his children and wife do not have inheritance rights to the inherited assets. The reason for this provision is because in the view of the people of Kampa District, Kampar Regency, when a man is not married, the one who looks after him, guarantees his life and is responsible for him is his family, while when a man is married he is usually more inclined to support his wife's family than his own family, because according to custom Kampa District, Kampar Regency, when a boy marries he will live with his wife's family. Judging from Islamic law, the customary provisions regarding the wife's inheritance rights from inherited property in Kampa District, Kampar Regency are a benefit based on mutual agreement. However, in practice, the wife's inheritance rights from inherited assets in the customs of Kampa District, Kampar Regency are contrary to Islamic inheritance law.